Neurokinin-1 receptor activation in globus pallidus - Chen, Lei; Cui, Qiao-Ling; Yung, Wing-Ho (Frontiers in Neuroscience, 2009)
The undecapeptide substance P has been demonstrated to modulate neuronal activity in a number of brain regions by acting on neurokinin-1 receptors. Anatomical studies revealed a moderate level of neurokinin-1 receptor in rat globus pallidus. To determine the electrophysiological effects of neurokinin-1 receptor activation in globus pallidus, whole-cell patch-clamp recordings were performed in the present study. Under current-clamp recordings, neurokinin-1 receptor agonist, [Sar9, Met(O2)11] substance P (SM-SP) at 1 μM, depolarized globus pallidus neurons and increased their firing rate. Consistently, SM-SP induced an inward current under voltage-clamp recording. The depolarization evoked by SM-SP persisted in the presence of tetrodotoxin, glutamate and GABA receptor antagonists, indicating its direct postsynaptic effects. The neurokinin-1 receptor antagonist, SR140333B, could block SM-SP-induced depolarization. Further experiments showed that suppression of potassium conductance was the predominant ionic mechanism of SM-SP-induced depolarization. To determine if neurokinin-1 receptor activation exerts any effects on GABAergic and glutamatergic neurotransmission, the action of SM-SP on synaptic currents was studied. SM-SP significantly increased the frequency of spontaneous inhibitory postsynaptic currents, but only induced a transient increase in the frequency of miniature inhibitory postsynaptic currents. No change was observed in both spontaneous and miniature excitatory postsynaptic currents. Based on the direct excitatory effects of SM-SP on pallidal neurons, we hypothesize that neurokinin-1 receptor activation in globus pallidus may be involved in the beneficial effect of substance P in Parkinson’s disease.